Improved solar energy photoactivity over defective BiOBr ultrathin nanosheets towards pollutant removal and oxygen evolution - Wu, Weibin (2021)
Defective BiOBr nanosheets with ultrathin thickness and surface-confined pits have been synthesized through a dual control of cetyltrimethylammonium bromide (CTAB) and polyvinyl pyrrolidone (PVP). The photocatalytic activity of the obtained defective BiOBr nanosheets was evaluated for the removal of rhodamine B (RhB), ciprofloxacin (CIP) and oxygen evolution from water. The as-prepared defective BiOBr nanosheets displayed significantly increased activity for pollutant degradation and oxygen evolution. The enhanced photocatalytic activity was ascribed to the improved light harvesting, suppression of charge recombination, and an increase in the number of active sites for photocatalytic reaction. The electronic structure of the defective BiOBr ultrathin nanosheets with confined pits has been tuned and thus varied the photocatalytic mechanism for pollutant degradation. The active species have changed from hole for BiOBr nanoplates to superoxide radical (O2.−) and hole for defective BiOBr nanosheets determined by ESR analysis and trapping experiments.